Rare earth metal boryl and gallyl compounds: synthesis and reactivity - Saleh, L; Liban Saleh (2014)
This Thesis describes the syntheses, characterisation and reactivity of rare earth metal boryl and gallyl compounds. Experimental and computational studies were performed to investigate the structure and bonding in these compounds. Chapter 1 introduces key metal-boryl and metal-gallyl compounds of the s, p, d and f-blocks via literature review. Chapter 2 describes the syntheses, structures and bonding analyses of rare earth metal boryl compounds. A short introduction to rare earth metal cations is given. Chapter 3 describes the syntheses, structures and bonding analyses of rare earth metal gallyl compounds. The preparation of a new class of rare earth metal cations will also be reported. A short introduction to rare earth metal amidinates is given. Chapter 4 presents reactivity studies of the rare earth metal gallyl compounds described in Chapter 3. To facilitate a direct structure and reactivity comparison, the corresponding boryl compounds were also synthesised. The results of a comprehensive DFT computational study to investigate the structure and bonding in these compounds are also presented. A short introduction to metal-element and metal-metal bond reactivity is given. Chapter 5 presents full experimental procedures and characterising data for the new compounds reported.